2012
DOI: 10.2215/cjn.04690511
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Determinants of Erythropoietin Deficiency in Chronic Kidney Disease

Abstract: on behalf of the NephroTest Study Group Summary Background and objectives Anemia in patients with CKD is highly related to impaired erythropoietin (EPO) response, the timing and determinants of which remain unknown.Design, setting, participants, & measurements This study measured EPO levels and studied their relation to GFR measured by 51Cr-EDTA renal clearance (mGFR) in 336 all-stage CKD patients not receiving any erythropoiesis-stimulating agent.Results In patients with anemia defined by World Health Organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 44 publications
4
66
0
Order By: Relevance
“…Decreased Epo levels in patients with CKD are obvious only when anemia is present but cannot be adequately elevated when hematocrit drops, suggesting that part of the Epo production capacity (i.e., through loss of Epo-producing cells) is irreversibly lost (53)(54)(55). In general, decreased Epo levels (typically assessed by ELISA in serum) correlate with severity of decreased excretory kidney function.…”
Section: Impaired Epo Production As Cause Of Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased Epo levels in patients with CKD are obvious only when anemia is present but cannot be adequately elevated when hematocrit drops, suggesting that part of the Epo production capacity (i.e., through loss of Epo-producing cells) is irreversibly lost (53)(54)(55). In general, decreased Epo levels (typically assessed by ELISA in serum) correlate with severity of decreased excretory kidney function.…”
Section: Impaired Epo Production As Cause Of Anemiamentioning
confidence: 99%
“…While Epo levels are better preserved in glomerular diseases than in interstitial diseases, suggesting that impaired Epo production is a direct consequence of interstitial disease (56), there is one exception as polycystic kidney disease is often associated with increased Epo production and polycythemia, due to aberrant HIF1a accumulation around cysts due to local hypoxia (57). Nevertheless, circulating Epo levels have been suggested as diagnostic marker of the extent of tubulointerstitial involvement in diabetic nephropathy (58), but due to superimposed regulating factors (including anemia, systemic inflammation, and reduced iron availability), utility of Epo levels as valid diagnostic marker for interstitial fibrosis could not be validated (53). Impaired Epo production as cause of anemia is not limited to CKD but is also increasingly being recognized as a cause of anemia in patients with diabetes mellitus.…”
Section: Impaired Epo Production As Cause Of Anemiamentioning
confidence: 99%
“…3 Surprisingly, in a large cohort of patients with CKD and anemia, circulating Epo levels were only moderately suppressed at early stages of disease compared with expected values. 4 In addition to kidney fibroblasts, liver cells and astrocytes may also synthesize Epo and thereby, contribute to circulating Epo levels. 5,6 This contribution may increase when the kidneys are unable to secrete sufficient Epo to maintain erythropoiesis, and an experimental report suggested that liver Epo synthesis is activated in mice suffering from chronic GN.…”
mentioning
confidence: 99%
“…8 Several patients with CKD displayed higher Epo levels than expected for their [Hb], suggesting that other factors than Epo deficiency may contribute to anemia of CKD. 4 Glycosylation changes may influence both Epo binding to its receptor and its half-life. 10,11 A higher PMI suggests less glycosylated Epo.…”
mentioning
confidence: 99%
See 1 more Smart Citation